The solubilities of major elements of fly ashes in the H3PO4 - Arslan, Mustafa; Boybay, Mustafa (My University, 1996)
Fly ash is mainly consist of calcium, iron, aluminum and silicon in the form of oxides, aluminates and silicates. A study has been conducted to determine the solubilities of the major elements (Ca, Al, Fe, Si) in the H3PO4. The work was carried out by using two typical fly ashes (Soma-B and Yeniköy in Turkiye) of low and high lime contents. The solubilities of elements are important point of view the recovery of elements and the utilization of fly ash. The effects of acid concentration, contact time, pH, temperature, solid/liquid ratio and particle size distribution on the solubilities of the elements were examined. The concentration of silicon in the solution was generally below detection limit. The maximum concentration of Al2O3, Fe2O3 and CaO for Soma-B fly ash are 5.47×10-2M (44.2%), 4.73×10-3M (51.1%) and 0.149M (97.9%), and for Yeniköy fly ash are 5.35×10-2M (98.5%), 7.97×10-3M (99.0%) and 0.376M (84.1%) respectively. The maximum concentration values except Fe2O3 (in 30% solution) were obtained in 40% aqueous of H3PO4. Other conditions were fixed as 5 g/100 ml acid, 60 min. and 25°C.
Keywords: Fly ash; Interaction of Fly ash-H3PO4; Solubility of Fly ash